A long-term culture model for investigating senescence-associated dysregulation in macrophages - Ruiz, Andy; Lucero-Gil, María Guadalupe; Torres, Martha; Juárez, Esmeralda (Frontiers in Immunology, 2025)
Macrophage senescence is increasingly recognized as a key contributor to immune dysfunction during aging and chronic inflammation. Here, we developed a reproducible long-term in vitro culture model to investigate the senescence’s phenotypic and functional consequences in human macrophages. Monocyte-derived macrophages (MDMs) were cultured for 7, 14, or 21 days and assessed for canonical senescence markers and immune function. While macrophages at day 7 exhibited minimal expression of β-galactosidase, H2AXpS139, and CDKN2A (p16INK4a), these markers were significantly upregulated at days 14 and 21, indicating progressive acquisition of a senescent phenotype. Cell viability remained above 95% across all time points, confirming the system’s stability. High-dimensional flow cytometry and unsupervised clustering revealed marked phenotypic remodeling over time, shifting from anti-inflammatory CD163+/CD206+ profiles to proinflammatory CD14+/CD64+/TLR2+ populations. Five distinct macrophage subpopulations were identified, each with dynamic temporal distribution and unique marker expression, highlighting a loss of plasticity and emergence of senescence-associated states. Functionally, day 7 macrophages produced a diverse cytokine panel responding to lipopolysaccharide (LPS), including IL-2, IL-12p70, IL-4, IL-5, TNF-α, GM-CSF, IFN-γ, and IL-10. In contrast, macrophages at days 14 and 21 displayed a markedly restricted cytokine profile, retaining the secretion of cytokines but significantly downregulating the secretion of Th1-type cytokines. This long-term culture model constitutes a robust, physiologically relevant tool to study immune aging, senescence-driven immune reprogramming, and inflammation in macrophages with the potential for the preclinical evaluation of therapeutic strategies to ameliorate inflammaging and restore immune competence.